Facile synthesis of β-NaGdF4:Yb/Er@CaF2 nanoparticles with enhanced upconversion fluorescence and stability via a sequential growth process1. Issue 31 (21st August 2015) - Ding, Bin-Bin; Liu, Kun; Zhang, Fu; Wang, Yang; Cheng, Sheng; Lu, Yang; Qian, Hai-Sheng
<x xml:space="preserve">Abstract</x> β-NaGdF4:Yb, Er@CaF2 core–shell nanoparticles: β-NaGdF4:Yb/Er nanoparticles coated with an ultrathin layer of CaF2 have been achieved via a sequential growth process.